Élie Halévy : Republican liberalism confronts the era of tyranny - Vincent, K. Steven (Intellectual history of the modern age., 2020)
In this densely contextualized biography, K. Steven Vincent describes how Élie Halévy (1870-1937), one of the most respected and influential intellectuals of the French Third Republic, confronted the Dreyfus Affair, World War I, and the rise of interwar totalitarianism while defending a distinctively French version of liberalism.